Knowledge and attitudes in dementia held by general practitioners in the primary care setting of Botucatu, São Paulo, Brazil - Vânia Ferreira de Sá Mayoral; Paulo José Fortes Villas Boas; Alessandro Ferrari Jacinto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Alzheimer's disease (AD) is the leading cause of dementia worldwide. Despite alarming evidence on dementia prevalence, the condition is still underdiagnosed by general practitioners (GPs) in primary care. Early detection of the disease is beneficial for patients and relatives, who should be provided comprehensive guidance on dealing with dementia complications, covering medical, family and social aspects, thereby providing an opportunity to plan for the future. Objective: The objective of this study was to assess the knowledge of and attitudes toward dementia held by GPs from a city in the interior of São Paulo State, Brazil. Methods: A non-randomized intervention study was conducted involving six lectures about dementia. Before and after the intervention, the participating physicians completed two quizzes about knowledge of and attitudes towards dementia. The study was carried out in the primary care services of the town and a total of 34 GPs participated in the study. Results: The mean age of the sample was 33.9 (±10.2) years and the majority (76.5%) of the sample had not undertaken medical residency training. The mean number of correct answers on the Knowledge Quiz about dementia before and after the training intervention was 59.6 and 71.2% (p<0.001), respectively. The comparison of the mean responses on the Attitude Quiz revealed no statistically significant difference between the two applications of the instrument, before and after intervention (p=0.059). Conclusions: More training for GPs on dementia should be provided.